2021
DOI: 10.3390/nano11071660
|View full text |Cite
|
Sign up to set email alerts
|

Complete Degradation and Detoxification of Ciprofloxacin by a Micro-/Nanostructured Biogenic Mn Oxide Composite from a Highly Active Mn2+-Oxidizing Pseudomonas Strain

Abstract: Ciprofloxacin (CIP), as a representative broad-spectrum antibiotic, poses a major threat to human health and the ecological environment as a result of its abuse and emissions. In this study, a highly active Mn2+-oxidizing bacterium, Pseudomonas sp. CCTCC M2014168, was induced to form micro-/nanostructured biogenic Mn oxide (BMO) aggregates through continuous culturing with 1 mmoL−1 Mn2+. Following the characterization of Mn4+ oxides and the micro-/nanostructures by scanning electron microscopy, high-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…When released into the environment untreated, CIP can also act as a pollutant. [1][2][3][4][5][6][7][8] The physicochemical characteristics of CIP are presented in Table S1 (ESI section). † Co-doped ZnS QDs were employed in the photocatalytic experiments to degrade CIP in water solutions.…”
Section: Qd-based Photocatalytic Degradation Of Cipmentioning
confidence: 99%
See 1 more Smart Citation
“…When released into the environment untreated, CIP can also act as a pollutant. [1][2][3][4][5][6][7][8] The physicochemical characteristics of CIP are presented in Table S1 (ESI section). † Co-doped ZnS QDs were employed in the photocatalytic experiments to degrade CIP in water solutions.…”
Section: Qd-based Photocatalytic Degradation Of Cipmentioning
confidence: 99%
“…Antibiotic contamination in wastewater and the environment can be reduced effectively via photocatalytic degradation when appropriate nanocatalysts are used. [4][5][6][7][8] In this direction, nanosized II-VI semiconductors have attracted much attention from researchers due to their unique physical characteristics and adequate optical bandgap, which endow them with effective photocatalytic activities. Among all other available semiconductors, zinc sulphide (ZnS) is the most interesting II-VI semiconductor owing to its stable cubic zinc blende crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“… 33 Analyses of degradation intermediates by HPLC and liquid chromatography/mass spectrometry suggested that 100% of CFX could be removed from water due to complete microbial degradation. 34 …”
Section: Resultsmentioning
confidence: 99%
“…The biodegradation of CFX likely started from the cleavage of isoxazole and piperazinyl rings catalyzed by sulfite reductase and cytochrome P450 (CYP450) enzymes, respectively . Analyses of degradation intermediates by HPLC and liquid chromatography/mass spectrometry suggested that 100% of CFX could be removed from water due to complete microbial degradation …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation